The Impact of Training Methodologies on Accountants’ Performance: An Empirical Assessment - Makwana, Prakashbhai N. (Journal of Global Economy, Business and Finance, 2026)
This study aims to explore the influence of different training methods on the performance of accountants in Sri Lanka. The study uses accountant's performance as the dependent variable while on-the-job training, off-the-job training, online training, mentoring and coaching and job rotation are considered the independent variables. The data was collected through questionnaires distributed online and analyzed using SPSS analysis methods such as descriptive statistics, reliability analysis, correlation analysis and regression analysis. The study concluded that on-the-job training, online training, mentoring and coaching and job rotation has a significant positive impact on the performance of accountants in Sri Lanka while off-the-job has an insignificant negative impact on performance. The study found that mentoring and coaching has the highest impact on accountants’ performance followed by on-the-job training, online training and job rotation. Based on the findings, the research recommends organizations to focus more on interactive and live training methods such as on-the-job training and mentoring and coaching. The study suggests that it is best to use a complete training approach that incorporates a variety of techniques in order to accommodate different learning styles.